HUBUNGAN DUKUNGAN PSIKOSOSIAL KELUARGA DENGAN TINGKAT STRES PASIEN HIV/AIDS - Girianto, Wiwik, Pria Wahyu Romadhon (Jurnal Kesehatan Mesencephalon, 2017)
Abstract : HIV/AIDS was one of psychosocial stressors in a persons life, because the disease was classified as chronic. The aims to determine the correlation between family support and HIV/AIDS patient stress level in Melati Ward Kediri General Hospital. Design was used correlation analytic with cross sectional approach. 20 respondents was taken by accidental sampling technique. Data were analyzed with Spearman rank test Â 0.05. The results showed nearly all respondents 80.0% less to get psychological support from family, and nearly half of the respondents 30.0% with moderate stress levels. Spearman rank test was obtained p value =0.024 that means there is a correlation between family support and HIV/AIDS patient stress level. Correlation coefficient was moderate (r = -0.503) with a negative direction. The level of stress on HIV/AIDS patient depends on their family support. The family as a support system of HIV/AIDS patient should be provide both moriil and material support to prevent high level of stress on HIV/AIDS.Keywords : family support, stress levels, HIV/AIDSÂ Abstrak : Penyakit HIV/AIDS merupakan salah satu stressor psikososial dalam kehidupan seseorang, karena penyakit ini tergolong kronis. Penelitian ini bertujuan untuk mengetahui hubungan dukungan keluarga dengan tingkat stres pasien HIV/AIDS di Ruang Melati RSUD Kab Kediri. Desain penelitian menggunakan analitik korelasional dengan pendekatan cross Sectional. Didapatkan sampel 20 respondendengan teknik accidental sampling. Data di analisis dengan uji rank spearman dengan =0,05. Hasil penelitian menunjukkan hampir seluruh responden (80%) kurang mendapatkan dukungan psikososial dari keluarga dan hampir setengah responden 30,0% dengan tingkat stress sedang. Hasil uji statistik diperoleh p value = 0,024 artinya ada hubungan dukungan psikososial keluarga dengan tingkat stres pada HIV/AIDS dengan nilai kekuatan hubungan sedang dan arah negative (r = -0,503). Tingkat stress pasien HIV tergantung padakoping masing-masing individu, dan dukungan keluarga hanya dapat sedikit membantu meringankan beban pasien. Keluarga sebagai pendamping terdekat pasien harus selalu siap memberikan bantuan baik moriil maupun materiil.Kata kunci : dukungan keluarga, tingkat stres, HIV/AIDS